Encounter with antigen-specific primed CD4 T cells promotes MHC class II degradation in dendritic cells - Furuta, Kazuyuki (National Academy of Sciences, 2012)
Major histocompatibility complex class II molecules (MHC-II) on antigen presenting cells (APCs) engage the TCR on antigen-specific CD4 T cells, thereby providing the specificity required for T cell priming and the induction of an effective immune response. In this study, we have asked whether antigen-loaded dendritic cells (DCs) that have been in contact with antigen-specific CD4 T cells retain the ability to stimulate additional naïve T cells. We show that encounter with antigen-specific primed CD4 T cells induces the degradation of surface MHC-II in antigen-loaded DCs and inhibits the ability of these DCs to stimulate additional naïve CD4 T cells. Cross-linking with MHC-II mAb as a surrogate for T-cell engagement also inhibits APC function and induces MHC-II degradation by promoting the clustering of MHC-II present in lipid raft membrane microdomains, a process that leads to MHC-II endocytosis and degradation in lysosomes. Encounter of DCs with antigen-specific primed T cells or engagement of MHC-II with antibodies promotes the degradation of both immunologically relevant and irrelevant MHC-II molecules. These data demonstrate that engagement of MHC-II on DCs after encounter with antigen-specific primed CD4 T cells promotes the down-regulation of cell surface MHC-II in DCs, thereby attenuating additional activation of naïve CD4 T cells by these APCs.